Konkretyzacja estetyczna w Zwierzętach nocy (2016) Toma Forda - Rojek, Patrycja (Przestrzenie Teorii, 2019)
Rojek Patrycja, Konkretyzacja estetyczna w Zwierzętach nocy (2016) Toma Forda [Aesthetic Concretization in Tom Ford’s Nocturnal Animals (2016)]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 401–416. ISSN 1644-6763. DOI 10.14746/pt.2019.32.22. The subject of Austin Wright’s novel Tony and Susan (published in 1993) is the reader’s experience. The peculiar relationship that forms between the main female character - a reader of literary fiction – and the novel itself as well as its author, inspired in 2016 Tom Ford to capture the specifics of the same relationships using the language of moving images. This article presents the effects of studying the complex system of communication situations occurring in the novel and its film adaptation: each of them contains an additional story around which further author-reader relationships are formed. The analysis shows that a significant part of the film’s plot is not a direct insight into the novel, but its concretization projected by a female protagonist. Tom Ford’s film is therefore considered in relation to Roman Ingarden’s theory on aesthetic concretization.